Structural and free volume characterization of sol–gel organic–inorganic hybrids, obtained by co‐condensation of two ureasilicate stoichiometric precursors. Issue 26 (20th February 2021) - Kavetskyy, Taras; Boev, Victor; Ilcheva, Vania; Kukhazh, Yuliia; Smutok, Oleh; Pan'kiv, Lyudmyla; Šauša, Ondrej; Švajdlenková, Helena; Tatchev, Dragomir; Avdeev, Georgi; Gericke, Eike; Hoell, Armin; et al.
Abstract: In this study two hybrid organic–inorganic ureasilicate monomers with different length of polymer segments were chosen for preparation of sol–gel material that includes two moieties blended on the molecular scale. The first monomer was obtained by crosslinking a double terminated polyoxyalkyleneamine with an isocyanate modified silicone ethoxide and the second one – by crosslinking between the isocyanate modified silicone ethoxide with an amino modified silicone ethoxide. Sol–gel route was applied for transformation of the liquid monomer blends in transparent materials with varying degree of rigidity. The prepared samples were characterized by small‐angle X‐ray scattering, Fourier‐transform infrared spectroscopy, positron annihilation lifetime spectroscopy, and swelling experiments. The results demonstrate that the structure of the obtained materials could be tuned by a simple variation of molar fraction ratio between these two monomers. This makes it possible to obtain nanostructured materials with predictable properties. Abstract :